Exercise in personal protective equipment in a hot, humid environment does not affect risk propensity. Issue 2 (2nd April 2016) - Schlader, Zachary J.; Temple, Jennifer L.; Hostler, David
ABSTRACT: We tested the hypothesis that heat stress created by light exertion in encapsulating personal protective equipment (PPE) in a hot, humid environment increases risk propensity. Ten healthy subjects (29 ± 7 y) completed 2 trials presented in a counter-balanced manner. Subjects donned encapsulating PPE, and in one trial they wore a tube-lined shirt underneath that was perfused with 5°C water. Subjects completed 2 15 min bouts of walking exercise on a treadmill at ˜50% maximal heart rate in a 32°C, 81% RH environment. Subjects completed the Balloon Analog Risk Task (BART), an objective measure of risk-taking, before, between the 2 exercise bouts, and following the final exercise bout. Personal cooling lowered (P < 0.01) mean skin temperature by 8.0 ± 1.6°C. Intestinal temperature rose (P < 0.01) in both trials, but was lower (P < 0.01) at the end of exercise in the cooling trial (38.0 ± 0.3°C vs. 37.6 ± 0.3°C). BART derived indices of risk propensity were not affected by trial or time (trial × time interaction: P ≥ 0.33). These data indicate that 60 min of exposure to mild heat stress created by light exertion in encapsulating PPE does not affect risk-taking behavior.